Coworking spaces vs. home: Does employees' experience of the negative aspects of working from home predict their intention to telework in a coworking space? - Lescarret, Colin; Lemercier, Céline; Le Floch, Valérie (Frontiers in Psychology, 2022)
In this study, we investigated the determinants of employees' intention to telework in a coworking space, with the assumption that employees' experience with the negative aspects of teleworking from home would impact their intention to telework in a coworking space in the future. A sample of 268 French teleworkers answered an online questionnaire measuring their experience of several negative aspects of teleworking from home (e.g., perceived social isolation), and their opinion toward teleworking in a coworking space (perceived usefulness, perceived feasibility, attitude and behavioral intention). Results indicate that perceived social isolation and perceived lack of working comfort when working from home directly impacted how useful participants perceived teleworking in a coworking space to be, and indirectly their intention to telework in a coworking space in the future. Budget, management agreement and job compatibility were, however, identified as factors mitigating participants' intention to telework in a coworking space, even if perceived as potentially beneficial.